Perception of Teachers and Students towards Shadow Education - Adhikari, Devi Prasad (The EFFORTS, Journal of Education and Research, 2022)
This paper explored perception of teachers and students on the practices and trends of shadow education. It is a qualitative study adopting narrative inquiry. Eight students studying Bachelor in Education (B. Ed.) and Bachelor in Business Studies (BBS) and five teachers teaching in different schools were purposively selected as informants. Semi-structured interviews were made to gather perception of the participants. The findings were illustrated in narrative and descriptive ways. The findings indicated that students and teachers perceived shadow education as the part of schooling that has prevailed in schools and colleges. The learners preferred private tutoring to formal regular classes as they found private tutoring more interactive and student centric than the formal classes. Additionally, this study indicated that the learners, teachers and authorities readily involve in shadow education. The implication of the present study is important for administrators, teachers, and students to make formal schooling more effective.